The Antifungal Activity of Lactoferrin and Its Derived Peptides: Mechanisms of Action and Synergy with Drugs against Fungal Pathogens - Fernandes, Kenya E.; Carter, Dee A. (Frontiers in Microbiology, 2017)
Lactoferrin is a multifunctional iron-binding glycoprotein belonging to the transferrin family. It is found abundantly in milk and is present as a major protein in human exocrine secretions where it plays a role in the innate immune response. Various antifungal functions of lactoferrin have been reported including a wide spectrum of activity across yeasts and moulds and synergy with other antifungal drugs in combination therapy, and various modes of action have been proposed. Bioactive peptides derived from lactoferrin can also exhibit strong antifungal activity, with some surpassing the potency of the whole protein. This paper reviews current knowledge of the spectrum of activity, proposed mechanisms of action, and capacity for synergy of lactoferrin and its peptides, including the three most studied derivatives: lactoferricin, lactoferrampin and Lf(1-11), as well as some lactoferrin-derived variants and modified peptides.